IoT Monitoring for Solar Powered Pump Applied in Hydroponic House - Yurika Islamiati; Tresna Dewi; Rusdianasari (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
Photovoltaic systems are used and utilized as electricity needs in many developed countries, including Indonesia. Currently, photovoltaic systems are an alternative source of electricity that is cheap, affordable and easy to apply in public facilities to use in laboratories. Public and government awareness of the decline in fossil fuels and pollution caused by the use of conventional power plants increases the application of renewable energy as an alternative greening in Indonesia. Technology is growing rapidly from year to year, one of which can be seen in the world of agriculture. This development has resulted in reduced farming land, especially in urban areas. So, there are several innovations that have emerged to increase crop productivity. With these problems, hydroponic techniques can be combined with IoT (Internet of Things) technology. The use of IoT is increasingly being used both on devices and in products that require connections such as wireless sensors, smart meters, and home automation systems. The quality of an IoT product can be seen from several parameters, namely low power consumption, longer range, wireless connectivity and higher data processing capabilities. IoT can be interpreted as communication between one device and another using the internet. This study provides recommendations for the utilization of PV system applications in the use of hydroponic plants and will display the results of data measurements in the field and discuss data on measuring battery voltage, current, power, solar panel voltage, solar current panels and irradiance.